Analysis of the Effect of No Work No Pay Policy on Employees of PT Taekwang Industrial Indonesia during the Covid-19 Pandemic - Diah Ayu Fitriah; Ely Agustin; Warmasih Warmasih; Silvy Sondari Gadzali; Abu Muna Almaududi Ausat (Journal on Education, 2023)
This research was conducted to determine the effect of the No Work No Pay policy on employees of PT. Taekwang is in a pandemic. The object of the research was carried out at the company PT. Taekwang Industrial. The method used is a qualitative research method using field research with a narrative approach, namely by focusing on studies interviewing informants who play a role in these conditions based on their experiences. Based on the research, the authors see the influence of NO Work No Pay on employees and companies. The data was obtained from experienced informants, namely employees and former employees of PT. Taekwang so that the data obtained is more accurate. From the results of the research above, it can be explained that the implementation of the No Work No Pay policy is effective and very influential for employees and companies during the Covid-19 Pandemic. However, by using the No Work No Pay policy, employees and companies are also affected. Starting from reducing orders for companies, and reducing working hours for employees who are still working, as well as laying off some employees who have worked for less than one year. From the description above, it can be concluded that the role of the No Work No Pay Policy is very important for employees and companies to survive in the midst of the Covid-19 pandemic